21 century sociology tradional core areas - Clifton D. Bryant, Dennis L. Peck (sage publication, 2007)
Since its inception through the early decades of the twentieth century, the discipline of sociology was essentially monolithic in perspective, representing a rather narrow range of interests into social problems areas. Early sociologists were essentially generalists, and during the first 100 years of disciplinary activity, the literature of sociology expanded only incrementally. By mid-twentieth century, however, there was a sufficiently large body of sociological literature on which to draw and a much broader and energized sociological curiosity as to foster some degree of specialization. With its new focus on theories of the middle range, sociological inquiry developed into a multifaceted perspective, representing a variety of specialty interests and an expanded literature in which a proliferation of knowledge is documented. Sociologists thus developed an expansive array of specialty knowledge that represents the variety of research and theoretical activity within the discipline. Now, in the twenty-first century, the success of the past century requires a comprehensive survey and assessment of the many specialty areas of sociology that is essential for organizing this vast information. The two-volume 21st Century Sociology: A Reference Handbook accomplishes this organization with 106 essays that are authored by leading authorities from the United States, Canada, Australia, the United Kingdom, Germany, Scotland, Sweden, The Netherlands, France, Spain, Finland, and Singapore. Each chapter provides an up-to-date, comprehensive survey of one of these specialty areas. The Handbook also represents a thorough inquiry into the state of knowledge and scholarly thinking in each of these specialty areas by offering authoritative insightful essays of the various subfields in sociology, provide an assessment of contemporary knowledge, and end with brief projections of anticipated future theoretical development and research activity. Several years ago, in response to the question â€œWhat is sociology?â€ a colleague responded, â€œSociology is what sociologists do.â€ As unusual a statement as this may appear to be, there is certainly an element of truth in it and perhaps even more than one might initially care to admit. Indeed, for more than 100 years, sociological inquiry has covered a vast terrain of topics, theoretical perspectives, and methodologies that run the range of mainstream areas of interest, emerging new ideas, as well as topics considered to be peripheral to the discipline but nevertheless draw heavily on sociological literature for their framework. The work sociologists engage in is both pure and applied, and depending on time and space and shifts in the dominant orientation of the body politic, the substance of this work is more or less significant. Like all things, the discipline of sociology and its practitioners are subject to the changing needs of the society that we attempt to better understand. Sociologists have been from the beginning social activists and social policy analysts. These interests and foci continue in the present and will undoubtedly continue throughout the twenty-first century. Increasingly, sociologists have engaged in exploring a wide range of topics, and this extensive activity is demonstrated through the large number of topical chapters presented in the Handbook. Thus, the model followed for this Handbook is one of inclusiveness in that a large number of topics are covered, but in so doing, the authors address each topic in a thorough, comprehensive manner. Although there is certain to be some modest theoretical and methodological overlap between some of the topics, each chapter is developed to reflect the unique historical development of the topic, offers a general overview of the current state of knowledge, and provides suggestions for how the area of inquiry is destined to develop as we move well into the twenty-first century. These topics are both interesting and informative in that the chapter content offers the reader insight into the rich legacy and development of the discipline of sociology while also providing the requisite reference information for advanced study and research into each substantive area. In this regard, there is a sufficient amount of information to support the rich sociological legacy of enabling public policy-oriented readers ample opportunity to learn while also providing important insights for those who enthusiastically embrace social activism as a part of the sociological enterprise.